A New Concept of Biotensegrity Incorporating Liquid Tissues: Blood and Lymph - Bruno Bordoni DPT, DO, PhD; Fabiola Marelli DPT, DO; Bruno Morabito DPT, DO, PhD; Roberto Castagna DPT, DO (SAGE Publishing, 2018)
The definition of fascia includes tissues of mesodermal derivation, considered as specialized connective tissue: blood and lymph. As water shapes rocks, bodily fluids modify shapes and functions of bodily structures. Bodily fluids are silent witnesses of the mechanotransductive information, allowing adaptation and life, transporting biochemical and hormonal signals. While the solid fascial tissue divides, supports, and connects the different parts of the body system, the liquid fascial tissue feeds and transports messages for the solid fascia. The focus of this article is to reconsider the model of biotensegrity because it does not take into account the liquid fascia, and to try to integrate the fascial continuum with the lymph and the blood in a new model. The name given to this new model is RAIN-Rapid Adaptability of Internal Network.